ANALISIS KESULITAN KETERAMPILAN MENULIS KARANGAN NARASI SISWA KELAS IV SDN 28/IV KOTA JAMBI - Astuti, Widia; Ika Panggih Wahyuningtyas; Sri Yulia Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Research findings show that students still face several difficulties in writing narrative essays. These difficulties include the inability to choose a title that matches the content of the writing, difficulty in finding and developing main ideas in sequence, the use of sentences with structures that are not yet appropriate according to the SPOK pattern, and errors in spelling and punctuation. Difficulties in writing narrative essays can be caused by internal and external factors. Internal factors include how students view the learning process, their enthusiasm for learning, and their study habits at home. Meanwhile, external factors include teachers' conventional teaching methods and a lack of support from families and the surrounding community. Therefore, more diverse writing learning efforts that focus on the process are needed so that students' story writing skills can improve. This study aims to examine the difficulties experienced by fourth-grade students at SDN 28/IV Kota Jambi when writing narrative stories. Writing is a useful language skill that requires the ability to convey thoughts clearly, use correct sentences, and apply writing rules and punctuation appropriately. This study takes a qualitative approach and uses a descriptive method. The subjects of this study consisted of 28 fourth-grade students in the 2026 academic year. Data collection techniques included story writing tests, interviews with teachers and students, observations, and document collection. The data were analyzed using descriptive qualitative analysis by looking at the students' writing from various aspects, namely title determination, idea development and paragraph formation, sentence structure, and the use of spelling and punctuation.